Theory of Change Thinking in Practice - Es, Marjan; Guijt, Irene; Vogel, Isabel (2015)
Want to know better how your interventions can contribute to change? A Theory of Change (ToC) approach helps in deepening your understanding - and that of your partners - of how you collectively think change ha ppens and what the effect will be of your intervention. Not only does it show what political, social, economic, and/or cultural factors are in play, it also clarifies your assumptions. Once a ToC has been devel oped, it can be used to continually reflect on it in ways that allow f or adaptation and checking of assumptions of your intervention. This u ser friendly guideline helps you to use a Theory of Change approach. T heories of change are the ideas and beliefs people have – consciously or not – about why and how the world and people change. How people per ceive and understand change and the world around them is infused by th eir underlying beliefs about life, human nature and society. They are deep drivers of people’s behaviour and of the choices they make. Socia l change processes are complex and characterised by non-linear feedbac k loops: our own actions interact with those of others and a myriad of influencing factors. This triggers reactions that cannot be foreseen and makes outcomes of change interventions unpredictable. Given these uncertainties, how can we plan strategically and sensibly? How can soc ial change initiatives move forward in emerging change processes in a flexible way, while remaining focused on the goal? In this context of complexity, Hivos has found a theory of change (ToC) approach useful i n guiding its strategic thinking and action, as well as its collaborat ive efforts with others. As it fosters critical questioning of all asp ects of change interventions and supports adaptive planning and manage ment in response to diverse and quickly changing contexts. It contribu tes to the quality and transparency of strategic thinking, and therefo re to personal, organisational and social learning. This guide builds on the experiences of Hivos working with a ToC approach. It is a pract ical guide for Hivos staff in applying a Theory of Change approach, bu t is also very useful for others working on social change such as soci al entrepreneurs and innovators. This guide builds on the work of a To C Learning Group initiated by Hivos and comprising of staff of the Cen tre for Development Innovation (CDI) of Wageningen University and Rese arch Centre and of experts Iñigo Retolaza Eguren, Isabel Vogel and Ire ne Guijt. For current thinking and work on the use of Theory of Change thinking in complex change processes, see http://www.theoryofchange.n l